Peran Wakaf Produktif Dalam Kesejahteraan Masyarakat - Masriyah, Siti (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study is to ascertain how beneficial productive waqf is to community welfare. employing research methodology, specifically a review of the literature on productive waqf for community welfare and using earlier studies as a guide. The article's findings demonstrate how waqf assets can be allocated for productive uses, which will undoubtedly boost local economic activity in a contemporary economic system and enhance community welfare. which is consistent with the primary goal of waqf, which is to distribute assets so that each Muslim can benefit from their wealth without favoring any particular group.